2001
DOI: 10.1897/1551-5028(2001)020<2802:teaiht>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Accumulation in Hawksbill Turtles (Eretmochelys Imbricata) and Green Turtles (Chelonia Mydas) From Yaeyama Islands, Japan

Abstract: Concentrations of 18 trace elements (V, Cr, Mn, Co, Cu, Zn, Se, Rb, Sr, Zr, Mo, Ag, Cd, Sb, Ba, Hg, Tl, and Pb) were determined in the liver, kidney, and muscle of green turtles (Chelonia mydas) and hawksbill turtles (Eretmochelys imbricata) from Yaeyama Islands, Okinawa, Japan. Accumulation features of trace elements in the three tissues were similar between green and hawksbill turtles. No gender differences in trace element accumulation in liver and kidney were found for most of the elements. Significant gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 0 publications
3
36
2
3
Order By: Relevance
“…In agreement with these findings, we observed that Cadmium concentrations in green turtle liver were similar to their food and that the Cu concentration in sea turtle liver was greater than in the stomach content. Similar relationships have been observed in green turtles from Japan (Anan et al, 2001). However, contrary to the findings of Maffucci et al, (2005), Zinc concentrations in the livers and kidneys of green turtles in our study were not significantly different from their stomach contents.…”
Section: Sea Turtle Tissue Comparisonssupporting
confidence: 72%
See 2 more Smart Citations
“…In agreement with these findings, we observed that Cadmium concentrations in green turtle liver were similar to their food and that the Cu concentration in sea turtle liver was greater than in the stomach content. Similar relationships have been observed in green turtles from Japan (Anan et al, 2001). However, contrary to the findings of Maffucci et al, (2005), Zinc concentrations in the livers and kidneys of green turtles in our study were not significantly different from their stomach contents.…”
Section: Sea Turtle Tissue Comparisonssupporting
confidence: 72%
“…The processes controlling the concentration and distribution of metals in coastal environments and their consequences in the species health are poorly understood. It is generally assumed that diet is the main source of metals to sea turtles (Caurant et al, 1999;Anan et al, 2001), but little is known of the process of metal accumulation in these species because data on metal residues in most components of sea turtles' diet has been lacking. As adults, green turtles forage largely on marine algae and seagrasses with variation in the diet due to the relative availability of food types over geographic and temporal scales (Garnett et al, 1985;Brand-Gardner et al, 1999;Seminoff et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em seus estudos concluiram que os animais carnívoros apresentam os níveis de metais comparativamente mais elevados que os herbívoros, corroborando com o trabalho de Sakai et al, (2000) em espécies de tartarugas marinhas Caretta caretta (carnívora) e Chelonia mydas (herbívora), avaliando metais em tecidos e diversos órgãos. Porém Anan et al (2001), concluíram que há similaridade entre os níveis de metais analisados nos rins, fígado e músculos de C. mydas e de E. imbricata, uma espécie herbívora e outra carnívora, respectivamente.A espécie E. imbricatas e se alimenta principalmente de crustáceos, moluscos,ouriços, esponjas e algas (MARCOVALDI et al, 2011) e é conhecido que organismos filtradores, como os moluscos, podem ser uma importante fonte de metais para outros organismos (GONÇALVES, FREIRE, NACIMENTO NETO, 2007;GALVÃO et al, 2009), e possivelmente a presença de Hg e Ba nas cascas dos ovos observados no presente estudo tenham sido transferidos pela fêmea depositante, ao qual adquiriram tais contaminantes por via alimentar. Sakai et al (1995), investigando os metais em diferentes tecidos de tartarugas marinhas da espécie C. caretta, concluíram que a utilização de ovos como uma ferramenta para o monitoramento pode ser utilizada, e acrescentam que os ovos que não conseguem desenvolver na fase inicial, permanecem no ninho, e podem ser mais adequadamente utilizados para o monitoramento de metais.…”
Section: Discussion/discussãounclassified
“…Matrix effects and instrumental drift of the ICP-MS were corrected by the element indium (In) as an internal standard (Anan et al, 2001). Se was assayed by a hydride generation AAS (HG-AAS) (Shimadzu, HVG-1 Hydride System).…”
Section: Methodsmentioning
confidence: 99%